Serum level of soluble urokinase plasminogen activator receptor (suPAR) as a disease severity marker of myasthenia gravis: a pilot study. (10th August 2020) - Uzawa, A.; Kojima, Y.; Ozawa, Y.; Yasuda, M.; Onishi, Y.; Akamine, H.; Kawaguchi, N.; Himuro, K.; Kuwabara, S.
Summary: Myasthenia gravis (MG) is an autoantibody‐mediated inflammatory disease of the neuromuscular junction. Biomarkers indicating disease activity in MG are warranted. Recently, the soluble urokinase plasminogen activator receptor (suPAR) has been reported to be associated with inflammation, tissue damage, disease activity and prognosis in various diseases, including autoimmune diseases. In this study, serum suPAR levels were measured in 40 patients with anti‐acetylcholine receptor antibody‐positive MG and 30 controls, and their correlations with clinical variables and severity scale scores were investigated. We identified that serum suPAR levels significantly correlated with MG activities of daily living scale (Spearman's ρ = 0·45; P = 0·004) and MG Foundation of America classification (Spearman's ρ = 0·37; P = 0·02) at serum sampling, but not with anti‐acetylcholine receptor antibody titers. In conclusion, serum suPAR levels can be a candidate for a novel biomarker of disease activity in anti‐acetylcholine receptor antibody‐positive MG. Abstract : Serum suPAR levels can be a candidate for a novel biomarker of disease activity in anti‐acetylcholine receptor antibody‐positive MG.